Glaucoma Characterization by Machine Learning of Tear Metabolic Fingerprinting. Issue 5 (7th April 2022) - Wu, Jiao; Xu, Mengqiao; Liu, Wanshan; Huang, Yida; Wang, Ruimin; Chen, Wei; Feng, Lei; Liu, Ning; Sun, Xiaodong; Zhou, Minwen; Qian, Kun
Abstract: Glaucoma is a common optic neuropathy disease affecting over 76 million people. Both timely diagnosis and progression monitoring are critical but challenging. Conventional characterization of glaucoma needs a combination of methods, calling for tedious procedures and experienced doctors. Herein, a platform through machine learning of tear metabolic fingerprinting (TMF) using nanoparticle enhanced laser desorption–ionization mass spectrometry is built. Direct TMF is obtained noninvasively, with fast speed and high reproducibility, using trace tear samples (down to 10 nL). Consequently, glaucoma patients are screened against healthy controls with the area under the curve (AUC) of 0.866, through machine learning of TMF. Further, primary open‐angle glaucoma (POAG) is differentiated from primary angle‐closure glaucoma (PACG) and an early‐stage POAG is identified. Finally, a biomarker panel of six metabolites for glaucoma characterization (including screening, subtyping, and early diagnosis) with AUC of 0.827–0.891 is constructed, showing related metabolic pathways. The work will provide insights into eye diseases not limited to glaucoma. Abstract : This work develops a high‐performance platform for glaucoma characterization through machine learning of tear metabolic fingerprinting, using nanoparticle enhanced laser desorption/ionization mass spectrometry in a noninvasive manner. Further, a metabolic biomarker panel is constructed and this work will contribute to advanced metabolic analysis of eye diseases.